Drug Therapy Problem and Contributing Factors among Ambulatory Hypertensive Patients in Ambo General Hospital, West Shoa, Ethiopia (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: drug therapy problem; hypertension; indication